Teachers’ Talk and EFL in University Classrooms - Rizkariani Sulaiman (Jurnal Studi Guru dan Pembelajaran, 2021)
The purpose of this study is to find the category of Teacher Talk (TT) in EFL (English as Foreign language) class at English Language Study Program at Indonesian Muslim University. Specifically for the Teacher Talk category, this study focuses on how many Teacher Talk categories appear in class for seven times each. This research was conducted in the EFL (English Education Study Program Class) Faculty of Literature at UMI. The participants of this study were 1 (one) English Education lecturer. While students who became participants were fifth semester students from C1 class that consists of 30 students. Data in this study were collected using video and audio recordings. Video and audio recordings are used to collect the Lecturer Teacher Talk category. Video recordings in this study were used to obtain a natural picture of class interaction. The results of this study are 7 categories of Teacher Talk displayed by Lecturers when interacting in class, namely: (1) starting or opening a class; (2) provide an explanation; (3) Give instructions; (4) Asking questions; (5) Encourage and motivate; (6) Provide Reinforcement; and (7) Closing.